FRI0329 The net-effect of combining rituximab with belimumab in severe systemic lupus erythematosus. (12th June 2018) - Teng, O.; Kraaij, T.; Kamerling, S.; de Rooy, E.; van Daele, P.; Bredewold, O.; Bakker, J.; Bajema, I.; Scherer, H.; Toes, R.; Huizinga, T.; Rabelink, T.; et al.
Abstract : Background: In systemic lupus erythematosus (SLE) patients, excessive formation of neutrophil extracellular traps (NETs) is observed while their degradation is impaired. In vitro, immune complexes (ICx) trigger NET formation while NET-derived DNA is a postulated autoantigen for anti-nuclear autoantibodies (ANAs), found in SLE. Based on these self-perpetuating mechanisms in SLE, we hypothesised that interfering with ICx formation should regress NET formation and potentially ameliorate disease. Objectives: Investigate the effect of Rituximab+Belimumab therapy on pathogenic autoantibodies in relation to NET formation in severe refractory SLE Methods: A phase 2A, open-label, single arm proof-of-concept study was performed wherein 16 SLE patients with severe, refractory disease were treated with a combination of CD20-mediated B-cell depletion with rituximab and sustained inhibition of B-cell activating factor with belimumab. Besides safety, the study's endpoints were chosen to address the concept of autoantibodies in relation to excessive NET formation. Results: We demonstrated that SLE-derived immobilised IgG, but not soluble IgG, induced excessive NET formation, confirming ex vivo that ICx mediate excessive NET formation in SLE. We showed that therapeutic intervention with RTX+BLM led to specific reductions in ANAs and regression of excessive NET formation. RTX+BLM appeared to be safe and achieved clinically significant responses: low lupus disease activity state was achieved in 10 patients, renal responses in 11 patients and concomitant immunosuppressive medication was tapered in 14 out of the 16 patients. Conclusions: This study provides novel insights into clinical beneficence of reducing excessive NET formation in SLE by therapeutic targeting ANA production with RTX+BLM. Altogether putting forward a new treatment concept that specifically ameliorates underlying SLE pathophysiology. Acknowledgements: We thank professor C. Pusey (Imperial College London, UK) for kindly providing the Syk inhibitor R406 for our experiments. Disclosure of Interest: O. Teng Grant/research support from: GlaxoSmithKline, Consultant for: Aurinia Pharmaceuticals, GlaxoSmithKline, T. Kraaij: None declared, S. Kamerling: None declared, E. de Rooy: None declared, P. van Daele: None declared, O. Bredewold: None declared, J. Bakker: None declared, I. Bajema: None declared, H. Scherer: None declared, R. Toes: None declared, T. Huizinga: None declared, T. Rabelink: None declared, C. van Kooten: None declared